Balancing Benefits and Risks of Long-Term Antiplatelet Therapy in Noncardioembolic Transient Ischemic Attack or Stroke. Issue 10 (26th July 2021) - Hilkens, Nina A.; Algra, Ale; Diener, Hans Christoph; Bath, Philip M.; Csiba, László; Hacke, Werner; Kappelle, L. Jaap; Koudstaal, Peter J.; Leys, Didier; Mas, Jean-Louis; Sacco, Ralph L.; Greving, Jacoba P.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Lifelong treatment with antiplatelet drugs is recommended following a transient ischemic attack or ischemic stroke. Bleeding complications may offset the benefit of antiplatelet drugs in patients at increased risk of bleeding and low risk of recurrent ischemic events. We aimed to investigate the net benefit of antiplatelet treatment according to an individuals' bleeding risk. Methods: We pooled individual patient data from 6 randomized clinical trials (CAPRIE [Clopidogrel Versus Aspirin in Patients at Risk of Ischemic Events], ESPS-2 [European Stroke Prevention Study-2], MATCH [Management of Atherothrombosis With Clopidogrel in High-Risk Patients], CHARISMA [Clopidogrel for High Atherothrombotic Risk and Ischemic Stabilization, Management, and Avoidance], ESPRIT [European/Australasian Stroke Prevention in Reversible Ischemia Trial], and PRoFESS [Prevention Regimen for Effectively Avoiding Second Strokes]) investigating antiplatelet therapy in the subacute or chronic phase after noncardioembolic transient ischemic attack or stroke. Patients were stratified into quintiles according to their predicted risk of major bleeding with the S2 TOP-BLEED score. The annual risk of major bleeding and recurrent ischemic events was assessed per quintile for 4 scenarios: (1) aspirin monotherapy, (2) aspirin-clopidogrel versus aspirin or clopidogrel monotherapy, (3) aspirin-dipyridamole versus clopidogrel, and (4) aspirin versus clopidogrel. Net benefit was calculated for the second, third, and fourth scenario. Results: Thirty seven thousand eighty-seven patients were included in the analyses. Both risk of major bleeding and recurrent ischemic events increased over quintiles of predicted bleeding risk, but risk of ischemic events was consistently higher (eg, from 0.7%/y (bottom quintile) to 3.2%/y (top quintile) for major bleeding on aspirin and from 2.5%/y to 10.2%/y for risk of ischemic events on aspirin). Treatment with aspirin-clopidogrel led to more major bleedings (0.9%–1.7% per year), than reduction in ischemic events (ranging from 0.4% to 0.9/1.0% per year) across all quintiles. There was no clear preference for either aspirin-dipyridamole or clopidogrel according to baseline bleeding risk. Conclusions: Among patients with a transient ischemic attack or ischemic stroke included in clinical trials of antiplatelet therapy, the risk of recurrent ischemic events and of major bleeding increase in parallel. Antiplatelet treatment cannot be individualized solely based on bleeding risk assessment.